2014
DOI: 10.5209/rev_fite.2014.v26.46970
|View full text |Cite
|
Sign up to set email alerts
|

Campo de deformación cortical actual de la Península Ibérica estimado a partir de medidas GPS

Abstract: We present the crustal deformation field in the Iberian Peninsula and northern Morocco, based on the analysis of the continuous GPS (CGPS) observations for the last five years, combined with the survey style observations (SGPS) of the CuaTeNeo network in eastern Betics. The analyzed CGPS stations come from several national and regional GNSS networks, with variable monument design and stability. Four CuaTeNeo campaigns were conducted with approximately a 4-year interval from 1997 to 2011. Although the calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This result was later confirmed by Rigo et al (2015), concluding that Iberia is nowadays attached to the Eurasian plate and that the continental collision that generated the Pyrenean range has waned. The data compiled by Khazaradze et al (2014) confirms the small to non-existent deformation in the northern and central parts of Iberia, increasing towards the south across the wide Africa/Eurasian plate boundary, where a relative motion of about 5 mm/y is accommodated. In this southern region, Koulali et al (2011) observed a relative west-southwest motion (2-3 mm/y) of sites located in the southwestern Betics with respect to the European plate and a clockwise rotation for stations in SW Betics and in Central Rif.…”
Section: Present-day Motion Of Iberiamentioning
confidence: 52%
“…This result was later confirmed by Rigo et al (2015), concluding that Iberia is nowadays attached to the Eurasian plate and that the continental collision that generated the Pyrenean range has waned. The data compiled by Khazaradze et al (2014) confirms the small to non-existent deformation in the northern and central parts of Iberia, increasing towards the south across the wide Africa/Eurasian plate boundary, where a relative motion of about 5 mm/y is accommodated. In this southern region, Koulali et al (2011) observed a relative west-southwest motion (2-3 mm/y) of sites located in the southwestern Betics with respect to the European plate and a clockwise rotation for stations in SW Betics and in Central Rif.…”
Section: Present-day Motion Of Iberiamentioning
confidence: 52%